Clean meat: How growing meat without animals will revolutionize dinner and the world - Jacobs, George (Ecolinguística: Revista brasileira de ecologia e linguagem (ECO-REBEL), 2019)
Shapiro, Paul. (2018). Clean meat: How growing meat without animals will revolutionize dinner and the world. New York, NY: Gallery Books.